Presence in absence: the ambiguous phenomenology of grief - Fuchs, Thomas (Phenomenology and the cognitive sciences, 2018)
Despite its complex experiential structure, the phenomenon of grief following bereavement has not been a major topic of phenomenological research. The paper investigates its basic structures, elaborating as its core characteristic a conflict between a presentifying and a ‘de-presentifying’ intention: In grief, the subject experiences a fundamental ambiguity between presence and absence of the deceased, between the present and the past, indeed between two worlds he lives in. This phenomenological structure will be analyzed under several aspects: (1) regarding bodily experience, as disruption of a shared intercorporeality; (2) as a loss of the shared world and shared habitualities, leaving the bereaved person with ubiquitous indications of absence and with a contraction of their own self; (3) regarding temporality, as a separation of two strands of time, namely a still ongoing past and an alienated present which become more and more desynchronized; (4) finally, as an “as-if presence” of the deceased which the bereaved continue to feel and sometimes to perceive, leading to a cognitive-affective conflict between two experienced realities. The transforming process of grief is then analyzed as a gradual adjustment to the loss, finally enabling a re-integration of the conflicting realities. This is achieved through an incorporation and identification with the deceased on the one hand, and through various forms of representation on the other hand, in particular by recollection and symbolization.